2004
DOI: 10.1002/humu.20012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants ofABCA1 modify Alzheimer disease risk and quantitative traits related to ?-amyloid metabolism

Abstract: Linkage studies have provided evidence that one or more loci on chromosome 9q influence Alzheimer disease (AD). The gene encoding the ATP-binding cassette A1 transporter (ABCA1) resides within proximity of previously identified linkage peaks and represents a plausible biological candidate for AD due to its central role in cellular lipid homeostasis. Several single nucleotide polymorphisms (SNPs) spanning ABCA1 have been genotyped and haplotype-based association analyses performed in four independent case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 45 publications
4
84
2
Order By: Relevance
“…We also note that an independent AD study suggested that the R variant was associated with earlier age-at-onset (AAO) in AD (Wollmer et al 2003). However, we observed no AAO effect in this sample, consistent with our previous observations (Katzov et al 2004) (data not shown).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…We also note that an independent AD study suggested that the R variant was associated with earlier age-at-onset (AAO) in AD (Wollmer et al 2003). However, we observed no AAO effect in this sample, consistent with our previous observations (Katzov et al 2004) (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…This may have a bearing on the success or failure of future studies that attempt to relate ABCA1 variation to other disease phenotypes, but may also serve as a point to revisit in large published studies, such as that of Frikke-Schmidt et al (2004). In particular, our own results on AD (Katzov et al 2004) and on CSF Ab 1-42 levels in the present study may be influenced by this potential modification. Unfortunately, it is uncommon for AD sample collection strategies to include information about smoking or other lifestyle data, and this is admittedly true for the majority of our own samples.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations